Perlindungan Hukum Terhadap Anak dalam Keluarga Poligami Ditinjau dari Hukum Islam dan Hukum Positif - Warsono Warsono (Postgraduate State Islamic Institute (IAIN) Metro, 2020)
This study aims to analyze the implementation of legal protection for children in polygamous families in terms of Islamic and positive law in Metro City, the inhibiting factors and efforts to overcome the obstacles that occur in polygamous families in terms of Islamic law and positive law in Metro City. This research is descriptive qualitative. Data collection was done by means of interviews and documentation. Data were analyzed by means of data reduction, data presentation and drawing conclusions. Based on the results of the analysis, the implementation of legal protection for children in a polygamous family in terms of Islamic law and positive, that is, legally positive has not been carried out well, but there is one family that is carried out, this is due to several factors, namely raising and caring for children, meeting all the necessities of life. and maintaining honor, responsibility, guiding and educating, as well as maintaining the health and welfare of children. Meanwhile, from Islamic law, there is something that is well implemented and also unlike the child's right to live, namely, children's rights in the clarity of their lines, children's rights in giving a good name, children's rights to obtain breast milk, children's rights to receive care, children's rights in property ownership. objects, children's rights in obtaining education and teaching. The factors that inhibit the needs of polygamous children, the educational factor of children in polygamous families, the factors of the relationship between children from polygamous families, and the factors of the relationship between children and parents. As well as efforts to overcome obstacles that occur in a polygamous family, namely upholding the husband's leadership in the family, the objectivity and neutrality of the husband, husband's justice, the husband acts wisely, the husband's love, the husband dares to give in for the sake of family harmony, the husband can maintain a balance of rights and obligations.